Effectiveness of microwave disinfection of complete dentures on the treatment of Candida-related denture stomatitis - Neppelenbroek, K. H.; Pavarina, Ana Claudia [UNESP]; Palomari Spolidorio, D. M. [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Spolidório, Luis Carlos [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2008)
The effectiveness of microwave disinfection of maxillary complete dentures on the treatment of Candida-related denture stomatitis was evaluated. Patients (n = 60) were randomly assigned to one of four treatment groups of 15 subjects each; Control group: patients performed the routine denture care; Mw group: patients had their upper denture microwaved (650 W per 6 min) three times per week for 30 days; group MwMz: patients received the treatment of Mw group in conjunction with topical application of miconazole three times per day for 30 days; group Mz: patients received the antifungal therapy of group MwMz. Cytological smears and mycological cultures were taken from the dentures and the palates of all patients before treatment at day 15 and 30 of treatment and at follow-up (days 60 and 90). The effectiveness of the treatments was evaluated by Kruskal-Wallis and Mann-Whitney tests. Microbial and clinical analysis of the control group demonstrated no significant decrease in the candidal infection over the clinical trial. Smears and cultures of palates and dentures of the groups Mw and MwMz exhibited absence of Candida at day 15 and 30 of treatment. on day 60 and 90, few mycelial forms were observed on 11 denture smears (36.6%) from groups Mw and MwMz, but not on the palatal smears. Miconazole (group Mz) neither caused significant reduction of palatal inflammation nor eradicated Candida from the dentures and palates. Microwaving dentures was effective for the treatment of denture stomatitis. The recurrence of Candida on microwaved dentures at follow-up was dramatically reduced.
Keywords: Candida; denture stomatitis; microwave; denture